Community-Based Ecotourism Development Strategy on Gili Ketapang Island, Probilinggo Regency - M. Dzacky Pradana Arifin; Harsuko Riniwati; Wike Wike (Postgraduate, University of Mataram, 2025)
The implementation of the Ecotourism Area on Gili Ketapang Island still has obstacles, one of which is the low level of community income, so an appropriate development strategy is needed. In addition, sustainability identification is carried out from existing social, economic and environmental aspects to determine aspects that require improvement and development. This research was conducted in This research is located in Gili Ketapang, Sumberasih District, Probolinggo Regency, East Java. The data analysis used is SWOT analysis. The ecotourism development strategy based on SWOT analysis is to apply the SO strategy in quadrant I. This strategy is that DYST collaborates with ecotourism managers on Gili Ketapang; DYST coordinates with related parties to provide expertise and knowledge development to tourism operators, the community and management; The government together with the management analyzes to determine the potential for developing suitable vehicles; Improving coordination between government and managers to improve ecotourism facilities and infrastructure; Community supervisory Groups involve the community in the management and development process; Create a planning strategy for sustainable ecotourism development.